2018
DOI: 10.1056/nejmoa1800965
|View full text |Cite
|
Sign up to set email alerts
|

Education Outcomes in a Duty-Hour Flexibility Trial in Internal Medicine

Abstract: BACKGROUND Concern persists that inflexible duty-hour rules in medical residency programs may adversely affect the training of physicians. METHODS We randomly assigned 63 internal medicine residency programs in the United States to be governed by standard duty-hour policies of the 2011 Accreditation Council for Graduate Medical Education (ACGME) or by more flexible policies that did not specify limits on shift length or mandatory time off between shifts. Measures of educational experience included observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
142
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 22 publications
8
142
0
4
Order By: Relevance
“…First, time-motion studies have demonstrated that internal medicine interns spend less than 15% of their time toward direct patient care. 38 It is possible that the demands of being an intern impeded their ability to perform more POCUS examinations on their patients, regardless of HUD access. Alternatively, the interns randomized to no personal access may have used the community device more frequently as a result of the lecture series.…”
Section: Discussionmentioning
confidence: 99%
“…First, time-motion studies have demonstrated that internal medicine interns spend less than 15% of their time toward direct patient care. 38 It is possible that the demands of being an intern impeded their ability to perform more POCUS examinations on their patients, regardless of HUD access. Alternatively, the interns randomized to no personal access may have used the community device more frequently as a result of the lecture series.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the directors of flexible programs were less likely to report dissatisfaction with multiple educational processes, including time for bedside teaching. There was no significant difference in the average scores (percent of correct answers) on in‐training examinations—68.9% in flexible programs and 69.4% in standard programs …”
Section: The Influence Of the Type Of Medical Training Program On Tramentioning
confidence: 93%
“…The iCOMPARE randomized trial was carried out in 63 internal medicine residency programs in the USA . Programs were randomized to use either the standard duty‐hour policies of the 2011 Accreditation Council for Graduate Medical Education (ACGME) or more flexible policies that did not include specific limits on the length of shifts or any mandatory time off between shifts.…”
Section: The Influence Of the Type Of Medical Training Program On Tramentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we may progressively find their attention dominated by electronic health records (EHR) that mediate their work and proxy for their patients. 1 Observational studies confirm an increasing shift from direct patient care to computer use in the wake of duty hour restrictions, 2,3,4 informing ongoing reforms into the structure of medical training. 5 Physicians report increasing time spent on paperwork and the computer 6 , alongside less time available for clinical interactions with patients.…”
Section: Introductionmentioning
confidence: 99%